ANALISIS INVESTIGASI FORENSIK SMARTPHONE ANDROID TERHADAP TINDAKAN CYBERCRIME MENGGUNAKAN FRAMEWORK DIGITAL FORENSIC MODEL BASED IN MALAYSIAN INVESTIGATION PROCESS - Kholifatulloh, M Alfalogika; Kusyanti, Ari; Trisnawan, Primantara Hari (Universitas Multi Data Palembang, 2024)
The usage of technology is becoming more important in this age of digitalization to assist daily living. Smartphone is one type of technology that is simple to use. Using simply a smartphone, many problems can be fixed. Financial issues, information access, online purchasing, etc. The usage of smartphone technology has advantages, but it can also have disadvantages. Cybercrime is a deficiency caused by smartphones. Online fraud is one of the many types of cybercrimes that exist in the real world. There are several types of Online Fraud, such as scams, phishing, carding, account takeovers, and much more. In this research, authors focus about online fraud that uses instant messaging and under the guise as an online investment. From these problems, there is digital forensic science that can be used as a solution to prove crime in cyberspace. In addition, digital forensic science aims to obtain valid digital evidence. By using the branch of digital forensic science, namely mobile forensics, this branch focuses on handling forensics related to mobile devices such as smartphones. To support problem solving, a Digital Forensic Model Based on Malaysian Investigation Process Framework is used which can help solve the problem of the case scenario being worked on.